Tertiary Performance, Field of Study and Graduate Starting Salaries - Chia, G.; Miller, Paul (Blackwell Publishing Asia, 2008)
This paper analyses data from the University of Western Australia (UWA) Graduate Destination Survey linked to information from the University's Student Records System to explore the determinants of graduates' starting salaries over the years 2002 to 2004. While the details examined also include age, gender, language spoken at home, country of birth, disability status and high school attended, most emphasis is placed on the impact on starting salaries of students' academic performance and their field of study. The analyses show that the main determinant of graduates' starting salaries is the weighted average mark they achieve at university. The salary differentials associated with higher marks in the Australian labour market appear greater than those reported in similar studies of the US and the UK labour markets. Science graduates are shown to have relatively low starting salaries, casting a shadow over recent suggestions that the supply of this group be increased through lower fee regimes.